The Relationship between Intellectual Capital and the Performance of Zakat Management Organizations - Hendra Kholid; Syafaat Muhari (Jurnal I-Philanthropy, 2026)
This study analyzes the relationship between intellectual capital and the performance of Zakat Management Organizations (ZMO/OPZ), comparing BAZNAS, which is managed by the government, and LAZ, which is managed by private institutions. The results of this study indicate that there is a positive and significant relationship between intellectual capital and the performance of Zakat Management Organizations (OPZ) in Indonesia during the period 2018 to 2022. Furthermore, the findings reveal differences in the relationship between intellectual capital and OPZ performance based on institutional ownership, namely between government-managed and privately managed OPZs. Private OPZs tend to demonstrate higher efficiency levels, particularly in managing human capital and capital employed, compared to government OPZs.